Immune Checkpoint Inhibitor in First-Line Treatment of Metastatic Renal Cell Carcinoma: A Review of Current Evidence and Future Directions - Tung, Iris; Sahu, Arvind (Frontiers in Oncology, 2021)
The incidence of renal cell carcinoma (RCC) is rising and metastatic RCC carries a very poor prognosis. The treatment paradigm for metastatic RCC has shifted dramatically in the last decade with multi-targeted tyrosine kinase inhibitors (TKI) previously used as first-line treatment but its utility is limited by short-lived efficacy and rapid disease progression. The dysregulation of immune cells in the tumour microenvironment contributes to unregulated growth of RCC. Thus, the use of immune checkpoint inhibitors has become first-line treatment for metastatic RCC and has offered dramatic improvement in clinical benefit and survival. Treatment with immune checkpoint inhibitor in combination with TKI appears to be promising in offering even greater response rates. The treatment for metastatic RCC continues to evolve and ongoing advances with new targeted agents and biomarkers are needed to continue to improve prognosis in the future.